Acupuncture for Dyspepsia Patients at the Griya Sehat Thabib Clinic Prof. Jim Bekasi - Putri, Ni Made Ayu Diana; Amal Prihatono,; Chantika Mahadini,; Puspo Wardoyo, (Jurnal Indonesia Sosial Sains, 2026)
Dyspepsia is a collection of symptoms related to gastroduodenal disorders, such as pain or burning in the epigastrium, postprandial fullness, upper abdominal bloating, and early satiety. Dyspepsia is classified into two types, namely organic dyspepsia and functional dyspepsia. Organic dyspepsia is accompanied by structural abnormalities such as gastritis, peptic ulcers, gastric cancer, gastroesophageal reflux disease (GERD), and gastric acid hypersecretion, whereas functional dyspepsia does not show abnormalities on physical examination or endoscopy. Dietary and lifestyle factors play a major role in the occurrence of dyspepsia, including the consumption of spicy, fatty, and baked foods; overeating; coffee consumption; smoking habits; alcohol intake; the use of anti-inflammatory drugs; and lack of physical activity. This study is qualitative research with a case study approach using a purposive sampling technique on one respondent. The measuring tool used was the change in dyspepsia symptoms before and after the intervention. The results showed that after four sessions of acupuncture therapy, there was a decrease in pain intensity and dyspepsia symptoms. Based on these results, acupuncture can be considered a complementary therapy for the treatment of dyspepsia in patients at the Griya Sehat Thabib Clinic Prof. Jim Bekasi.